Imaging and Pathology Study of the Chemotherapy Regression Area of Hepatoblastoma – A Prospective Single-Center Study. (3rd July 2020) - Shen, Gang; Wu, Linlin; Zhao, Jie; Wei, Bin; Zhou, Xianjun; Zhuo, Xiaoying; Dong, Qian
Abstract: Objective: The objective of this study is to determine the frequency of no residual cancer tissue in the chemotherapy regression area (CRA) of hepatoblastoma after preoperative chemotherapy and to measure the distance between the tumor capsule and the residual cancer nests. Methods: All the tissues in the CRAs of the resected specimens were excised. HE staining and immunohistochemical staining were performed to determine the frequency of residual cancer tissue in the CRA, and the distances between the residual cancer nests and the tumor capsule were measured. Results: A total of 30 patients were included in the study. The tumor volume decreased after chemotherapy by an average of 619 ml. Of the 30 patients, the CRAs of 18 still had residual cancer nests. The longest distance between the residual cancer nest and tumor capsule was 11.2 mm. Conclusions: After chemotherapy, 60% of patients still had residual cancer nests in CRAs, the furthest distance was 11.2 mm.